The Relationship Between Activity Daily Living Level And Quality Of Life Of Geriatric Patients In RSUP Dr. Mohammad Hoesin Palembang - Linata, Angela Maria; Jalalin (Sriwijaya Journal of Medicine, 2020)
Background The quality of life of the elderly is influenced by several factors such as physical health, psychological health,and good social relationships. Physical health is related to daily living activities that a person does in his daily lifeincluding ambulation, eating, dressing, bathing, brushing teeth and making up. At old age, a person will experience adecrease in physical condition which will affect the value of fulfilling one's daily living activities. This study aims toanalyze the relationship between the level of independence of daily living activities and the level of quality of life ofgeriatric patients. Methods: This study was an observational analytic study with a cross sectional design. The sampleswere geriatric patients in Dr. Mohammad Hoesin Palembang in September-October 2019. The sample of this study was55 respondents. Results: From 55 Geriatric patients in Dr. Mohammad Hoesin Palembang found 60% male respondentsand 40% female respondents, the 60-74 years age group as much as 74.5%, the 75-90 year age group as much as 25.5%,the 50-60 year age group as much as 26%. Chi-square test results showed a significant relationship between the level ofActivity Daily Living and the level of quality of life of geriatric patients (p value = 0.000). The results of the odds ratio ingeriatric patients state that the probability of improving the quality of life is 27.7 times greater in patients who have anindependent daily living activity level than in patients who have a total dependent daily living activity level. In theanalysis, it was also found that the level of daily living activity of geriatric patients is a protective factor for the quality oflife of geriatric patients. (95% CI = 0.006-0.206). Conclusion: There is a significant relationship between the level of dailyliving activity and the quality of life of geriatric patients in , dr. Mohammad Hoesin Palembang.